2021
DOI: 10.1007/s12529-021-09970-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Risk Perceptions and Affective Consequences in COVID-19 Protective Behaviors

Abstract: Background Slowing the spread of the novel coronavirus (COVID-19) requires behavioral changes such as physical distancing (e.g., staying a 6-foot distance from others, avoiding mass gatherings, reducing houseguests), wearing masks, reducing trips to nonessential business establishments, and increasing hand washing. Like other health behaviors, COVID-19 related behaviors may be related to risk representations. Risk representations are the cognitive responses a person holds about illness risk such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…Speculatively, this could happen if people do not believe that they can cope effectively with the coronavirus crisis. Furthermore, these findings dovetail with prior research [ 5 ] that showed how negative affective responses stemmed out from the perceived risk of suffering the coronavirus were associated with engagement in COVID-19 related risk behaviors, such as having houseguests and shopping.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Speculatively, this could happen if people do not believe that they can cope effectively with the coronavirus crisis. Furthermore, these findings dovetail with prior research [ 5 ] that showed how negative affective responses stemmed out from the perceived risk of suffering the coronavirus were associated with engagement in COVID-19 related risk behaviors, such as having houseguests and shopping.…”
Section: Discussionsupporting
confidence: 85%
“…Recommendations included a range of behaviors that can be distinguished into preventative (i.e., hygiene behaviors such as hand washing, cleaning surfaces with alcohol-based disinfectants, sneezing and/or coughing in a tissue or elbow), and avoidant (i.e., physical distancing such as avoiding crowded places, home working and distance learning) conducts [ 4 ]. In this regard, Alegria, Fleszar-Pavlović, Ngo, et al [ 5 ] differentiated among COVID-19 related risk behaviors—such as having houseguests and shopping—and increased protective behaviors—for instance, hand washing. In specifics, examples of recommended preventative behaviors in Italy were washing hands often using soaps or alcohol-based solvents, not touching eyes, nose, and mouth with hands, sneezing and/or coughing in a tissue or elbow, using the face masks; in addition, examples of recommended avoidant behaviors were avoiding close contact with people, maintaining an interpersonal distance of at least one meter, avoided crowded places, leaving the house and traveling only for valid and urgent reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, those who perceived themselves to be highly susceptible were inclined to reduce social contact (7). Alegria et al identified positive correlation between frequency of washing hands with self-perceived effectiveness of washing hands and epidemic risk perception based on the Common-Sense Model of Self-Regulation (CSM-SR) (8). Chinese college students were associated with a relatively high risk perception toward COVID-19 in the study of Ding et al, especially in female students and non-medical students as 92.5% of them believed that those in good health condition may be infected with COVID-19, and 85.1% of the college students were concerned about members of their family becoming infected (9).…”
Section: Introductionmentioning
confidence: 99%
“…Following the fear appeal theory of public health (Witte & Allen, 2000), we assume that one major psychological function of governmental restrictions is increasing people's COVID-19 LOCKDOWN MEASURES AND PROTECTIVE FACTORS perception of risk of getting infected, so that they engage in preventive behaviors (Rogers, 1975;Tagini et al, 2021) such as social distancing or hand washing (e.g., Alegria et al, 2021). In addition, lockdown-dependent perceived risk of infection might be a stressor (Prati & Mancini, 2021) inducing depressive symptoms (Kim et al, 2021) and health anxiety (Mohd et al, 2021).…”
Section: Strict Vs Mild Lockdown Measures In Romania Vs Hungary and Their Psychological Consequencesmentioning
confidence: 99%